Assessment of Tree Species Diversity, Biomass, C and N Storage in Two Sites of Dry Tropical Forest of Chhattisgarh, India - Mexudhan; Jiwan Lal; Gunjan Patil (International Journal of Economic Plants)
The present study was conducted in Katghora and Pali Sites in the dry tropical forest of Chhattisgarh, India. The experiment was conducted on Katghora Forest division in July 2018 to June 2019. The stratified random sampling technique was used for quantifying the tree layer vegetation. The results revealed that density and basal area varied from 278 to 333 stems ha-1 and 16.18 to 19.38 m2 ha-1 and was more in Katghora site as compare to Pali site. The concentration of dominance, Shannon index, equitability, species richness and beta diversity ranged from 0.33–0.60, 1.43–2.31, 0.57–0.88, 3.95–4.39 and 2.94–4.17, respectively in Katghora and Pali sites. The stand biomass of tree layer vegetation ranged from 214.65–246.06 t ha-1 in which above ground tree component (AGTC) ranged from 149.66–171.25 t ha-1 and below ground component (BGTC) ranged from 64.99-74.83 t ha-1. The similar pattern in total C storage of tree layer component ranged from 90.51–103.64 t ha-1 in which AGTC of C storage ranged from 67.29-76.91 t ha-1 and BGTC of C storage ranged from 23.22–26.74 t ha-1. The total N storage of tree layer vegetation ranged from 1277.70–1451.93 kg ha-1 in which AGTC of N storage ranged from 913.78–1032.90 kg ha-1 and BGTC of N storage ranged from 363.92–419.03 kg ha-1. The density, basal area, biomass, C storage and N storage was more in Katghora site as compare to Pali site due to more disturbance such as cattle grazing, illegal felling, collection of fuel wood, fodder and NTFPs etc.